SERPENTINITIC MéLANGES ASSOCIATED WITH HP AND UHP ROCKS IN CENTRAL ASIA - Dobretsov N.L.; Buslov M.M. (My University, 2004)
Serpentinitic mélanges containing eclogites, blueschists, and jadeitic rocks have been studied within the following foldbelts: Borus (West Sayan), Chagan-Uzun (Gorny Altai), Chara (East Kazakhstan), Kokchetav (North Kazakhstan), and Maksyutov (Southern Urals). The West Sayan (Borus belt) and Gorny Altai (Chagan-Uzun belt) are Caledonian foldbelts formed after collisions of paleo-seamounts with primitive island arcs, which resulted in the exhumation of eclogites and jadeitic rocks. The Chara belt of Hercynian age was formed during the Late Carboniferous-Permian collision of the Siberian and Kazakhstan continents and represents a strike-slip zone comprising serpentinitic mélanges and HP units of different ages. In Caledonian time, the mélanges represent an accretionary wedge at the margin of the Kazakhstan continent. The Kokchetav and Maksyutov foldbelts of, respectively, Caledonian and Hercynian ages resulted from collision of microcontinents with island arcs and formation of sheeted complexes incorporating large lenses of UHP-HP rocks and less serpentinitic mélanges.Two types of serpentinitic mélange occur in all suture zones formed as a result of collision of island arcs with seamounts or other island arcs. Type I mélange contains HP rocks in antigorite or olivine-talc-antigorite schists associated with high-temperature mantle peridotites, which can be regarded as part of the hanging wall of a paleosubduction zone. Type II mélange is a part of an obducted oceanic crust and contains blocks and inclusions of LP and LT metamorphic rocks associated with island arc and/or seamount terranes. The suture zones formed by continent/island arc or microcontinent collision (the Kokchetav megamélange and the lower unit of the Maksyutov complex) comprise no large sheets of serpentinitic mélange, but only subordinate lenses of mélanges with HP rocks (the Maksyutov lower unit) or small and sporadic ultramafic lenses inside a tectonic mélange with a metasedimentary matrix.